2003
DOI: 10.1104/pp.102.017483
|View full text |Cite
|
Sign up to set email alerts
|

RNA Expression Profiles and Data Mining of Sugarcane Response to Low Temperature

Abstract: Tropical and subtropical plants are generally sensitive to cold and can show appreciable variation in their response to cold stress when exposed to low positive temperatures. Using nylon filter arrays, we analyzed the expression profile of 1,536 expressed sequence tags (ESTs) of sugarcane (Saccharum sp. cv SP80-3280) exposed to cold for 3 to 48 h. Thirty-four cold-inducible ESTs were identified, of which 20 were novel cold-responsive genes that had not previously been reported as being cold inducible, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
14

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 88 publications
4
108
0
14
Order By: Relevance
“…This is consistent with the inference from the present study, where the ability to maintain photosynthetic rate during chilling correlates with increases in the amount of PPDK. In addition, a stress-induced (drought-induced and cold-induced) increase in PPDK expression has been shown in previous studies of other C4 species (Michalowski et al, 1989;Moons et al, 1998;Nogueira et al, 2003). For example, a RNA profile of cold-responsive genes using filter arrays showed that PPDK transcripts significantly increased on transfer of a sugar cane hybrid (Saccharum sp.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the inference from the present study, where the ability to maintain photosynthetic rate during chilling correlates with increases in the amount of PPDK. In addition, a stress-induced (drought-induced and cold-induced) increase in PPDK expression has been shown in previous studies of other C4 species (Michalowski et al, 1989;Moons et al, 1998;Nogueira et al, 2003). For example, a RNA profile of cold-responsive genes using filter arrays showed that PPDK transcripts significantly increased on transfer of a sugar cane hybrid (Saccharum sp.…”
Section: Discussionmentioning
confidence: 96%
“…In the case of Arabidopsis, a dicot model, it was revealed a down-regulated expression pattern promoted by high-salinity stress for AtUCP4 and AtUCP5 ( S EKI et al, 2002). However, other abiotic stresses as low and high temperatures (NANTES et al, 1999;NOGUEIRA et al, 2003;SWIDZINSKI et al, 2002) drought, wound (CHEONG et al, 2002 induced up-regulation in AtUCP genes. These results are puzzling but it could be suggested a differential regulation at cell or tissue/organ level among different species.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity, as several others biotic and abiotic stresses, alters the equilibrium between the production and the scavenging of ROS (GILL; TUTEJA, 2010; MUNNS; TESTER, 2008;PANG;WANG, 2008;PARIDA;DAS, 2005). ROS are produced continuously in different cellular compartments such as chloroplast, mitochondria and peroxisomes and their imbalance cause oxidative damage to membrane lipids, proteins, and nucleic acids (ASHRAF, 2009;BANU et al, 2009;JEZEK;HLAVATÁ, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations